Soft drink cans clipping as fibre reinforcement in concrete mix - Muhammad Amar Aizat, Abdullah (2014)
Reinforced concrete structure still face the same problem of uncontrolled flexural strength that can allow cracks occurred on the structure surface and can reach to the reinforcement bar. This problem can be overcome by adding some additive materials such as fiber. This study was conducted to examine hardened properties of plain concrete and fibers reinforced concrete based on wet properties and mechanical properties. The second objective is to determine the flexural behavior and mid-span deflection of soft drink cans fiber reinforced concrete beam and conventional beam. Two percentages (1% and 3%) of aluminum fiber based on weight of cement were incorporated to the mix design. Aluminum is the most abundant metal in the earth's crust. It is produced from bauxite, a clay-like ore that is rich in aluminum compounds. The performance of cube was analyzed in term of their compressive strength and the values increase with increase the length of curing days, but the fiber amount for the mix in more than 1% makes the bond between cement and aggregates less. The cylinder was testing in term of their indirect tensile strength and the result show increment significantly by about 1% at 28 days. For the rest of mixes, adding fibers has no major effect. Soft drink cans aluminum fiber reinforced concrete can be used to achieve the concrete performance in term of flexural strength. Flexural behavior of soft drink cans aluminum fiber reinforced concrete and plain concrete are much better compared to theoretical in term of ultimate load. All the results for mid-span deflection also achieved the theory calculation based on ACI 318-05. The soft drink cans aluminum fiber controls the cracking behavior of the specimens. Although the soft drink cans aluminum fiber reinforced concrete beam has more cracks compare to plain concrete, but the crack width is smaller.